THE RELATIONSHIP BETWEEN 119Sn NMR RESONANCE DUE TO ADDITIONAL METHYLENE GROUPS OF DICARBOXYLIC ACID DERIVATIVES OF TRIPHENYLTIN(IV) COMPLEX AND THE RESULTS OF CYTOTOXICITY TESTS ON HUMAN PROMYELOCYTIC LUEKEMIC CELLS - , Teoh Siang Guan and Yip Foo Win ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
The complexes of triphenyltin(IV) derivatives of malonic acid (MaH), succinic acid (ScH), glutaric acid (GtH) and adipic acid (DpH) were successfully synthesized and obtained in solid form. The free ligands and complexes were characterized quantitatively using C, H and Sn elemental analysis as well as spectroscopic methods such as infrared (FTIR) and nuclear magnetic resonance (1H, 13C &amp